Pharmacophore Analysis of Monoterpene Melaleuca leucadendra as an Inhibitor for 3CLPro of the SARS-CoV-2 - Syarifah, Ismi Farah; Suryani, Yani; Adzani, Ghea Gema; Kurniawan, Isma Dwi; Taupiqurrohman, Opik (Jurnal Biodjati, 2022)
The monoterpene compound has been reported to have antiviral activities . This study aimed to test the monoterpene compound in Melaleuca leucadendra to inhibit the SARS-CoV-2 virus. The monoterpenes tested were Î±-Pinene, Î²-Pinene, Linalool, Î±-Terpineol, and Terpinene-4-Ol. The method used was computational through pharmacophore analysis. The indicator for the quality of the compound was the fit score. A fit score of more than 50% indicates a good-quality compound, while a fit score of less than that indicates aÂ  poor-quality compound. Based on the analysis results, the monoterpene compound in Melaleuca leucadendra can potentially inhibit the SARS-CoV-2 virus directly through the inhibition of 3C-like protease. The linalool showed a fit score of 55% with interactions of hydrophobic, electrostatic, and hydrogen bonds. All the compounds did not inhibit the metabolic process and were safe, possibly having no side effects based on ADMET analysis.